2015
DOI: 10.1063/1.4922737
|View full text |Cite
|
Sign up to set email alerts
|

Agar-polydimethylsiloxane devices for quantitative investigation of oviposition behaviour of adult Drosophila melanogaster

Abstract: Drosophila melanogaster (fruit fly) is a model organism and its behaviours including oviposition (egg-laying) on agar substrates have been widely used for assessment of a variety of biological processes in flies. Physical and chemical properties of the substrate are the dominant factors affecting Drosophila's oviposition, but they have not been investigated precisely and parametrically with the existing manual approaches. As a result, many behavioral questions about Drosophila oviposition, such as the combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Young flies that enclosed from the pupae within half a day were collected into new stock bottles and aged for 5 days in the same condition. When transferring flies on the day of the experiment, 25 female and 20 male flies (consistent with our previous work 45 ) were first anesthetized using ether and counted. The flies were given a minimum of 1 hour recovery time prior to each assay.…”
Section: Fly Stockmentioning
confidence: 91%
See 2 more Smart Citations
“…Young flies that enclosed from the pupae within half a day were collected into new stock bottles and aged for 5 days in the same condition. When transferring flies on the day of the experiment, 25 female and 20 male flies (consistent with our previous work 45 ) were first anesthetized using ether and counted. The flies were given a minimum of 1 hour recovery time prior to each assay.…”
Section: Fly Stockmentioning
confidence: 91%
“…We have recently introduced a sensitive miniaturized tool which provided the capability to quantify oviposition behavior of adult stage and free-flying Drosophila in response to physical properties of the substrate. 45 We used PDMS membranes with controlled-size through-holes to pattern laboratory agar substrates with desirable oviposition sites in which the flies showed a strong area-and stiffnessdependent egg laying behavior. This technique has the potential for development of decision making behavioral and toxicological chemical screening devices due to the use of agar, a fly-attractant porous gel, through which chemicals can be infused controllably.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research performed by researchers showed how fruit fly larvae respond to heavy metals present in food [69]. A group of researchers studied oviposition (i.e., egg-laying) of the adult fruit fly [7,70]. Adult fruit fly has also been studied for observing how they and choose and approach the path for the food [7,57].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Microfluidic technology has recently emerged as a powerful tool for neural and behavioral investigation of small model organisms such as C. elegans, [35][36][37][38][39][40][41][42] D. melanogaster, [43][44][45][46] and D. rerio. [47][48][49][50][51][52][53] Most recently, various microfluidic techniques have been introduced for precise manipulation, stimulation, and monitoring of zebrafish larvae's behavior.…”
mentioning
confidence: 99%